Josephus a unique witness - Bentley-Taylor, David (Ross-shire, UK Christian Focus, 1999)
Includes bibliographical references and index.
Keywords: Josephus, Flavius, -- 37-c.100 -- biography; Josephus -- criticism, interpretation, etc